Implementasi Kebijakan Pelayanan Keprotokolan di Kementerian Koordinator Bidang Pembangunan Manusia dan Kebudayaan - Hendriyana, Ricki (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study aims to analyze the implementation of protocol service policies at the Coordinating Ministry for Human Development and Culture as a strategic instrument in supporting good governance. Using a descriptive qualitative research design based on institutional case studies, data were collected through in-depth interviews, participant observation, and analysis of official documents. The results indicate that protocol services have a dual function—administrative and symbolic—reflecting the legitimacy and public image of the bureaucracy. Policy implementation is supported by formal regulations, experienced human resources, and relatively adequate infrastructure. However, obstacles remain, including limited trained staff, a limited budget, and suboptimal adaptation to the demands of digitalization and hybrid event management. The study also found that innovations such as the development of e-protocol applications and the implementation of digital service models contribute significantly to increasing efficiency and transparency. These findings confirm that the success of protocol implementation is largely determined by a combination of apparatus professionalism, technological support, and cross-sector coordination. This study provides a theoretical contribution by positioning protocol within a policy-based public service framework, while also providing practical recommendations for strengthening bureaucratic reform in the digital era.